Benign tumor finding in Temporomandibular Joint: Cone Beam CT application and radiographical features of suspected condylar osteochondroma - Indri Kusuma Dewi; Aga Satria Nurrachman; Lusi Epsilawati (Ikatan Radiologi Kedokteran Gigi Indonesia, 2021)
Objectives: This case report is aimed to present a finding of a benign tumor at the Temporomandibular Joint (TMJ) area involving the condylar head of the mandible that radiographically showed the typical features of osteochondroma using and emphasizing on the application of Cone Beam CT (CBCT) imaging. Case Report: A 24-year-old female patient came to the Radiology Department of Unpad Dental Hospital as referred from her previous dental surgeon to get CBCT examination of her entire right side of mandible with a provisional diagnosis of mandibular hyperplasia. Conclusion: Osteochondroma and condylar hyperplasia are often clinically difficult to differentiate, CBCT imaging can easily distinguish the enlargement of condylar head in condylar hyperplasia with irregular condylar mass and altered trabecular pattern in osteochondroma. CBCT may be helpful in establishing the diagnosis of condylar tumors originating from bone.